Security Challenges for Digital Transformation in Saudi Arabia - Assiri, Khalid; Almdani, Khalid; Al Saeedi, Hassan; Softah, Abdullah; Khogeer , Sultan (International Journal of Scientific Research and Management (IJSRM), 2022)
Saudi organizations are increasingly using digital technologies. Despite widespread efforts to benefit from digitalization, few companies can claim to have seen significant results. Organizational employees have been linked to the success or failure of the digitization process in a growing body of studies.  Three hypotheses regarding the security of the digital transition have been suggested in this study. These hypotheses include determining how security has evolved because of the increased use of digital systems, as well as determining the best risk management strategies. A range of public and private Saudi entities will get an electronic survey as part of this study.  In summary, we have found that as the digital transformation grows, the security risk increases as well, necessitating the implementation of a robust security system and the most effective risk management measures. Additionally, the business must include employees in the development and implementation of the digital transformation to maintain their loyalty. Additionally, all employees must understand and agree on the digital transformation goals, objectives, and plans. Successful business leaders can build a compelling vision, unite, and engage staff to adopt new methods of doing business.